A new treatment of alopecia induced by palbociclib: Topical cetirizine. (March 2021) - Caro, Gemma; Fortuna, Maria C; Magri, Francesca; Federico, Alessandro; Carlesimo, Marta; Rossi, Alfredo
Introduction: Recently CDK4/6 inhibitors have been introduced for the treatment of hormone positive breast cancer resistant to endocrine therapy. Among their side effects, alopecia is often reported being associated to patients' distress and depressive symptoms. Case Report: We report the case of a 70-year-old woman affected by breast cancer in treatment with Palbociclib, who developed alopecia. Management and Outcome: We prescribed a topical solution with cetirizine. Global photography, trichoscopy and trichogram were assessed. All evaluations demonstrated alopecia improvement. Discussion: Currently, no treatment options for CDK 4/6 inhibitors induced alopecia have been proposed. Herein, we report the use of topical cetirizine.